Work Environment: Unveiling Job Satisfaction Through Work Stress Among Honorary Employees in Offices of Education - Afiq, Muhammad Farid; Turnip, Kaiman; Lubis, Rahmi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Enhancing employee productivity is primarily dependent on job satisfaction. Multiple studies have investigated elements that contribute to employee job satisfaction, such as the work environment. Nevertheless, prior research findings have displayed a lack of consistency, leading to current debates within the academic community. Researchers hypothesize that additional elements may influence the correlation between the work environment and job satisfaction, thus necessitating further analysis. A correlational method was utilized to collect data from a sample of 149 honorary employees. The data were evaluated using structural equation modeling (SEM) with the assistance of SmartPLS 3.0. The findings indicated the following: (1) a strong and statistically significant correlation exists between the Work Environment and employee Job Satisfaction; (2) there is also a positive and significant correlation between Job Stress and employee Job Satisfaction; (3) a positive and significant correlation was observed between the Work Environment and employee Work Stress; (4) Work stress plays a mediating role in positively and significantly influencing the relationship between the work environment and the job satisfaction of honorary employees. This study enhances the existing body of knowledge by providing fresh empirical evidence on the correlation between work environment and job satisfaction, with job stress acting as a mediator.